2017
DOI: 10.1055/s-0043-113572
|View full text |Cite
|
Sign up to set email alerts
|

Driving Under the Influence of Antidepressants: A Systematic Review and Update of the Evidence of Experimental and Controlled Clinical Studies

Abstract: This review provides an update of experimental and clinical studies on the effects of antidepressants on driving performance. A systematic literature search on the PubMed database (1980-2016) was performed. Twenty-eight studies could be included in this review, whereas only 5 studies investigated driving performance under antidepressants in patients. Most tri- and tetracyclics have acute deleterious effects on driving performance that, except for mianserin, attenuate after subchronic use. Selective serotonin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…On the other hand, the conclusions obtained by Ravera et al [10] and Brunnauer et al [8,14] when analyzing different experimental studies indicate that SSRIs do not present a high risk for driving vehicles, unless treatment is at high doses or there is concomitant consumption with other DIMs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the conclusions obtained by Ravera et al [10] and Brunnauer et al [8,14] when analyzing different experimental studies indicate that SSRIs do not present a high risk for driving vehicles, unless treatment is at high doses or there is concomitant consumption with other DIMs.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, SSRIs have practically replaced TCAs due to their greater tolerability and safety [13]. Studies report on Odds Ratios (OR) from 1.10 to 3.10 for the risk of a traffic accident when being under antidepressant treatment [14], which highlights the risk of increasing doses of TCAs [15][16][17][18] as a clear relation involving exclusively the use of TCAs that is not confirmed [19]. On the other hand, among studies that assessed the influence of non-sedative antidepressants, such as SSRIs and venlafaxine, a slight or no increase in the risk of traffic accidents was found [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Elvik suggested a 35% increased risk of traffic crashes involving personal injury from antidepressant use (Elvik 2013 ). Recent clinical studies have shown that modern antidepressants improve or at least stabilise the driving skills of persons with depression (Brunnauer et al 2021 ; Brunnauer and Laux 2013 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Miyata et al ( 2018 ) found that partly remitted depressive patients treated with antidepressants (monotherapy and combination) do not differ from healthy controls concerning the performance of Wisconsin Card sorting test, TMT, and Continuous Performance Test. Brunnauer and Laux ( 2017 ) found, based on a systematic literature review, that SSRIs and serotonin-norepinephrine reuptake inhibitors (SNRIs) venlafaxine and milnacipran did not affect driving ability.…”
Section: Introductionmentioning
confidence: 99%